Kajian karakteristik, status gizi dan konsumsi makanan sumber protein pada ibu hamil di Kabupaten Jayapura - Bela, Sarni Rante Allo; Mollet, Genoveva Chatleen Copenhagenia (Poltekkes Kemenkes Aceh, 2024)
Background: High-risk pregnancy occurs when a pregnant woman experiences increased health risks during pregnancy. This condition is influenced by several factors, including the mother's age being too young or too old, short gestation, frequent childbirth, and nutritional problems such as Chronic Energy Deficiency (CED). In Papua Province, the prevalence of CED in pregnant women reached 25.78%, higher than the national average. In addition, the prevalence of CED in Jayapura Regency is much higher than the national and provincial averages of 36.94%.Objectives: To investigate the age, gestational age, parity, and nutritional status of high-risk pregnant women, and to examine their consumption patterns of protein-rich foods.Methods: The type of research used is descriptive observational research with a cross-sectional design. This research was conducted at the Dosay Health Center, Waibhu Health Center, Sentani Health Center, and Harapan Health Center in Jayapura Regency, from June to August 2023. The study population included all pregnant women in the working area of the Health Center in the first and second trimesters, totaling 183 pregnant women, with a sample size of 105 pregnant women selected through purposive sampling. Data collected included the age of the pregnant women, the interval between pregnancies, parity, and nutritional status using BMI and upper arm circumference (Lila), along with dietary intake of protein sources, gathered using a Food Frequency Questionnaire. Data analysis was carried out using univariate statistical tests using SPSS 16. Results: Among 105 sample, the majority had a risk age > 35 (52,4%). Pregnancy interval > 3 years (48,6%), parity < 4 (53,1%), good nutritional status (42,9%), upper arm circumference ≥ 23,5 cm (83,8%) and diet Insufficient protein sources (78,1%).Conclusion: The percentage of pregnant women with good nutritional status is quite low (42,9%) and most have a diet lacking in protein sources (78,1%). This condition emphasizes the need for improved nutrition and health education to ensure safe pregnancy and childbirth. Keywords :Nutrition for pregnant women, protein consumption, protein sources